On the approximation properties of Cesàro means of negative order of double Vilenkin – Fourier series - Tepnadze, T. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5We establish approximation properties of Cesàro $% (C,-α ,-β)$ means with $α ,β $ $ε $ $(0,1)$ of Vilenkin\,--\,Fourier series. This result allows one to obtain a condition which is sufficient for the convergence of the means $σ _{n,m}^{-α,-β }(x,y,f)$ to $f(x,y)$ in the $L^{p}$-metric.